Effect of Cassia Auriculata Hot Infusion (Herbal Tea) on Mathumekam (Diabetic) Patients - A Pilot Study - Anpuchelvi, S.; Sritharan, G. (Proceedings of Jaffna Science Association, 2010)
Cassia auriculata has been widely used in Siddha medicine as avara panchangam chroornam and the main constituent of herbal tea. In folk remedies avarai panchangam of Cassia auriculata are supposed to be having anti-diabetic activity from literature survey. It is recommended in diabetes. The best quality of Csssia auriculata leaves, flowers, seeds, bark and root were purified first. Then the ingredients were dried in sunlight. Dried ingredients were later roasted in low flame. It is then powdered and packed in airtight containers. The present pilot study was planned to find out the effect of the clinical efficacy and safety of Cassia auriculata herbal tea in the management of diabetic mellitus. All the patients selected for the study were registered after their detailed history and thorough clinical examination. The study was conducted with the consent of the patient in Jaffna and they were informed about the study drug, its effects, duration of the trial, and overall plan of the study. The patients were included in the clinical study only after issuing written informed consent. Twenty patients of either sex, between the ages of 40 - 60 years with Type - II diabetes mellitus were selected for the clinical trial. 5g Cassia auriculata herbal tea powder is dissolved in 180 ml of hot water at the time of administration. After the collection of initial FBS (Fasting blood sugar), Cassia auriculata herbal tea hot infusion (powder 5g) were administered two times a day for a fortnight. Similar dietary instruction was given to the Patients. The fasting blood sugar measurements were taken baseline, after 1st wk and 2nd wk of the trial. All adverse events were recorded with information about severity, date of onset, duration and action taken regarding the drug, except for two patients who complained of nausea. There were no other reported side effects of the drug. Statistical analysis was done. All values are expressed as mean +/- SD. Difference between means were tested. This study helped to observe the results of fasting blood sugar levels among diabetic patients treated with Cassia auriculata herbal tea. The FBS values for patients treated with Cassia auriculata herbal tea are: initial 186.67 +/- 7.28 mg/dl, 1st wk 162.42 +/- 4.32 mg/dl and final 146.47 +/- 3.52 mf/dl. In the case of patients using Cassia auriculata herbal tea, a decrease in fasting blood sugar level is observed. The present pilot study should be extended into a detailed study with a larger sample size and longer duration to evaluate the Cassia auriculata herbal tea's hypoglycaemic actions and also its effects on microaluminuria and lipid profile.
Keywords: Diabetes mellitus; Cassia auriculata; Siddha medicine